2010
DOI: 10.1007/s11064-010-0314-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute 17β-Estradiol Pretreatment Protects Against Abdominal Aortic Occlusion Induced Spinal Cord Ischemic-Reperfusion Injury

Abstract: Postoperative neurologic deficit due to spinal cord ischemia-reperfusion (I/R) injury is the most devastating complication following thoracoabdominal aortic aneurysm repairs. The protective potential for 17β-Estradiol has not been yet studied in such injury. In this study, ischemia induction for 18 min in male New Zealand White rabbits resulted in the highest percentage (80%) of biphasic paraplegic outcome assessed by Tarlov's score. Acute Estradiol pretreatment (1 mg/kg, i.p., 30 min before I/R induction) alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
2
4
0
2
Order By: Relevance
“…In our present study, spinal cord ischemia significantly decreased the SOD and catalase levels in the spinal cord at 72 h after I-R. This result is consistent with previous studies that showed that I-R injury in the rabbit spinal cord significantly decreased the activities of SOD and catalase at 48 [35] and 72 h [21] post-ischemia. However, some experiments showed that SOD and CAT activities in the ischemic spinal cord were induced in response to I-R injury [34,36].…”
Section: Discussionsupporting
confidence: 93%
“…In our present study, spinal cord ischemia significantly decreased the SOD and catalase levels in the spinal cord at 72 h after I-R. This result is consistent with previous studies that showed that I-R injury in the rabbit spinal cord significantly decreased the activities of SOD and catalase at 48 [35] and 72 h [21] post-ischemia. However, some experiments showed that SOD and CAT activities in the ischemic spinal cord were induced in response to I-R injury [34,36].…”
Section: Discussionsupporting
confidence: 93%
“…23 Some patients experience acute spinal cord dysfunction following thoracic aortic occlusion as a result of acute spinal cord ischemia from hypoperfusion during crossclamping. 16 In the English literature, the protective potential of curcumin has not yet been investigated in spinal cord ischemia-reperfusion injury induced by abdominal aortic occlusion. The aim of this study was to evaluate the Effects of curcumin on acute spinal cord ischemia-reperfusion injury in rabbits neuroprotective effects of curcumin on the acute phase of spinal cord ischemia-reperfusion injury.…”
mentioning
confidence: 99%
“…Activation of caspase-3 is considered to be a reliable marker for apoptotic cell death [1][2][3][4][5] and is also involved in differentiation of neural and hematopoietic cells [6,7]. In the motor neuron cell line of the spinal cord, the treatment of caspase-3 inhibitor attenuates the toxicity of multi-catalytic proteasome inhibitor lactacystin [8].…”
Section: Introductionmentioning
confidence: 99%